Formation of a room temperature stable Fe-V(O) complex: reactivity toward unactivated C-H bonds - Ghosh, Munmun; Singh, Kundan K.; Panda, Chakadola; Weitz, Andrew; Hendrich, Michael P.; Collins, Terrence J.; Dhar, Basab B.; Sen Gupta, Sayam (Journal of American Chemical Society, 2014)
An Fe-V(O) complex has been synthesized from equimolar solutions of (Et4N)(2)[Fe-III(Cl)(biuretamide)] and mCPBA in CH3CN at room temperature. The Fe-V(O) complex has been characterized by UV-vis, EPR, Mossbauer, and HRMS and shown to be capable of oxidizing a series of alkanes having C-H bond dissociation energies ranging from 99.3 kcal mol(-1) (cyclohexane) to 84.5 kcal mori (cumene). Linearity in the Bell-Evans-Polayni graph and the finding of a large kinetic isotope effect suggest that hydrogen abstraction is engaged the rate-determining step.

Spectroscopic and reactivity comparisons of a pair of bTAML complexes with Fe-V=O and Fe-IV=O units - Pattanayak, Santanu; Jasniewsk, Andrew J.; Rana, Atanu; Draksharapu, Apparao; Singh, Kundan K.; Weitz, Andrew; Hendrich, Michael; Que, Lawrence, Jr.; Dey, Abhishek; Sen Gupta, Sayam (Inorganic Chemistry, 2017)
In this report we compare the geometric and electronic structures and reactivities of [Fe-V(O)](-) and [Fe-IV(O)](2-) species supported by the same ancillary nonheme biuret tetraamido macrocyclic ligand (bTAML). Resonance Raman studies show that the Fe-O vibration of the [Fe-IV(O)](2-) complex 2 is at 798 cm(-1), compared to 862 cm(-1) for the corresponding [Fe-V(O)](-) species 3, a 64 cm(-1) frequency difference reasonably reproduced by density functional theory calculations. These values are, respectively, the lowest and the highest frequencies observed thus far for nonheme high-valent Fe-O complexes. Extended X-ray absorption fine structure analysis of 3 reveals an Fe-O bond length of 1.59 angstrom, which is 0.05 angstrom shorter than that found in complex 2. The redox potentials of 2 and 3 are 0.44 V (measured at pH 12) and 1.19 V (measured at pH 7) versus normal hydrogen electrode, respectively, corresponding to the [Fe-IV(O)](2-)/[Fe-III(OH)](2-) and [Fe-V(O)](-)/[Fe-IV(O)](2-) couples. Consistent with its higher potential (even after correcting for the pH difference), 3 oxidizes benzyl alcohol at pH 7 with a second-order rate constant that is 2500-fold bigger than that for 2 at pH 12. Furthermore, 2 exhibits a classical kinteic isotope effect (KIE) of 3 in the oxidation of benzyl alcohol to benzaldehyde versus a nonclassical KIE of 12 for 3, emphasizing the reactivity differences between 2 and 3.